Synthesis by Reversed Phase Transfer Catalysis and Characterization of Naphthol AS-D Pigment - Eleonora Cornelia Crasmareanu; Vasile Simulescu; Gheorghe Ilia (Journal of Chemistry)
Reversed phase transfer catalysis (RPTC) was applied to synthesize the Naphthol AS-D pigment. This method consists in the transfer of the aryldiazonium cation 4-nitrobenzenediazonium from aqueous medium into the organic phase (nitrobenzene) in the form of a lipophilic ions pair by the catalyst used (perfluorooctyl potassium sulfonates). In the organic phase the azo-coupling reaction between 4-nitrobenzenediazonium chloride and 3-hydroxy-2-carboxylic acid 2-methyl-anilide (Naphthol AS-D) takes place as coupling component. Using this unconventional method of synthesis, an increase of the reaction rate, combined with a higher purity of the product, was obtained.